2012
DOI: 10.1101/gr.131912.111
|View full text |Cite
|
Sign up to set email alerts
|

A-to-I editing of microRNAs in the mammalian brain increases during development

Abstract: Adenosine-to-inosine (A-to-I) RNA editing targets double-stranded RNA stem-loop structures in the mammalian brain. It has previously been shown that miRNAs are substrates for A-to-I editing. For the first time, we show that for several definitions of edited miRNA, the level of editing increases with development, thereby indicating a regulatory role for editing during brain maturation. We use high-throughput RNA sequencing to determine editing levels in mature miRNA, from the mouse transcriptome, and compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
88
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 47 publications
(65 reference statements)
13
88
0
1
Order By: Relevance
“…In wild-type worms, few small RNAs are produced over these regions while abundant small RNAs are observed in adr-1;adr-2 mutant animals, suggesting that ADAR competes with the RNAi machinery to engage these substrates, a recurring theme in multiple studies (Ekdahl et al 2012;Vesely et al 2012;Warf et al 2012). The authors determined that a subset of ARLs (184) was edited, suggesting there might be overlap between our data sets.…”
Section: Comparison Of Eer Data Sets With Data Sets Of Related Studiesmentioning
confidence: 99%
“…In wild-type worms, few small RNAs are produced over these regions while abundant small RNAs are observed in adr-1;adr-2 mutant animals, suggesting that ADAR competes with the RNAi machinery to engage these substrates, a recurring theme in multiple studies (Ekdahl et al 2012;Vesely et al 2012;Warf et al 2012). The authors determined that a subset of ARLs (184) was edited, suggesting there might be overlap between our data sets.…”
Section: Comparison Of Eer Data Sets With Data Sets Of Related Studiesmentioning
confidence: 99%
“…We have previously shown that A-to-I RNA editing increases in both coding and non-coding substrates in the developing mouse brain (Ekdahl et al, 2012;Wahlstedt et al, 2009). To study the mechanisms that regulate A-to-I editing during neuronal maturation, we isolated cortical neural progenitor cells from mouse cortices at embryonic day 16 and cultured them for up to 14 days in vitro (DIV).…”
Section: Rna Editing Increases In Cultured Primary Cortical Neurons Amentioning
confidence: 99%
“…S1A). To determine if editing increased in a similar way in developing cultured neurons as in the brain, coding as well as non-coding RNA substrates with both specific and overlapping specificity for ADAR1 and ADAR2 editing were selected for analyses after 1-12 days in culture (Ekdahl et al, 2012;Nishimoto et al, 2008;Ohlson et al, 2007). Similar to that in the embryonic brain, low levels of editing were observed at the I/M site in the coding region of the Gabra-3 transcript and at the +6 site in the miRNA precursor transcript pri-miR-376b after 1 DIV (Fig.…”
Section: Rna Editing Increases In Cultured Primary Cortical Neurons Amentioning
confidence: 99%
See 2 more Smart Citations